Evaluating the impact of urban green spaces on public well-being and environmental sustainability in Saudi Arabian megacities - Abdullah Addas (Discover Sustainability)
Abstract Urban green spaces (UGSs) are crucial for enhancing environmental sustainability and promoting public well-being, particularly in rapidly urbanizing desert megacities like Riyadh and Jeddah, Saudi Arabia. The study aims to assess the impact of UGSs on mental and physical health, social cohesion, and local climate regulation, emphasizing how socio-demographic factors such as gender, income, and age affect UGS accessibility and usage. The study implemented a mixed-methods approach by integrating Geographic Information System (GIS) mapping and structured surveys utilizing a 5-point Likert scale with 384 residents. Additionally, semi-structured interviews were conducted with urban planners and policymakers. Results reveal that 72% of participants reported significant mental health improvements linked to UGS use, and areas rich in green spaces demonstrated a temperature reduction of up to 4.8 °C. However, socio-economic disparities were evident, with low-income neighborhoods having limited and poorly maintained UGSs compared to affluent areas. Findings indicate that accessibility issues are particularly pronounced among women and older populations. Policy recommendations are provided, focusing on the equitable distribution of UGSs and adopting sustainable design practices to mitigate urban heat and enhance public health. These recommendations align with Saudi Vision 2030’s goals of fostering urban livability and resilience. Future research should undertake longitudinal studies to assess the long-term health benefits of UGSs and explore innovative, water-efficient irrigation systems suitable for arid environments.